A Comparison on Numerical Simulation Models for Vibrational Performances of the Wood Truss Joist Floor System. (23rd July 2021) - Shen, Yinlan; Zhou, Haibin; Xue, Shuo; Zhang, Jinchuan
Abstract : Wood truss joist floors are increasingly used to replace traditional solid timber joist floors in low-rise timber houses. An understanding of the vibration performance of wood truss joist floors is critical for the design and serviceability of the floors. It is difficult to model wood truss joist floors accurately because of the complicated boundary conditions and numerous sophisticated flexible connections. This paper discusses three simplified modeling methods for the wood truss joist floor system. The modeling results were validated by a series of static deflection tests and vibration modes and frequencies tests of a full-size floor. And predictive analysis of human-induced vibration of the floor was also conducted. The vibration characteristics of the wood truss joist floor were investigated. The examination of the applicability of these modeling methods was provided. The results indicate that the point loading deflection more easily affects the deflection of the adjacent joist. However, the deflection influence on other joists that are three spaces away is minimal. Walking on the wood truss joist floor produces steep vibration acceleration fluctuations at the floor center for a relatively long time period. The sheathing-to-joist connections and the metal plate connections of the joists have significant influences on the vibration response of the wood truss joist floor. The modeling method, which considers the flexible metal plate connections and flexible sheathing-to-joist connections, performs best for predicting the vibration performance of the floor.